2012
DOI: 10.1007/s10549-012-2108-3
|View full text |Cite
|
Sign up to set email alerts
|

Adult weight gain, fat distribution and mammographic density in Spanish pre- and post-menopausal women (DDM-Spain)

Abstract: High mammographic density (MD) is a phenotype risk marker for breast cancer. Body mass index (BMI) is inversely associated with MD, with the breast being a fat storage site. We investigated the influence of abdominal fat distribution and adult weight gain on MD, taking age, BMI and other confounders into account. Because visceral adiposity and BMI are associated with breast cancer only after menopause, differences in pre- and post-menopausal women were also explored. We recruited 3,584 women aged 45–68 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…The negative association we observed between anthropometric factors and percent density or dense area is consistent with the literature [21][22][23][24][25][26][27][28][29][30], although more conflicting results are reported for dense area [21,[24][25][26][27][28][29][30], possibly due to important variation in the adjustments performed in the analyses. Interestingly, this inconsistency is also illustrated in our results by the inversion of the correlations between adiposity and dense area after adjustment for non-dense area.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The negative association we observed between anthropometric factors and percent density or dense area is consistent with the literature [21][22][23][24][25][26][27][28][29][30], although more conflicting results are reported for dense area [21,[24][25][26][27][28][29][30], possibly due to important variation in the adjustments performed in the analyses. Interestingly, this inconsistency is also illustrated in our results by the inversion of the correlations between adiposity and dense area after adjustment for non-dense area.…”
Section: Discussionsupporting
confidence: 90%
“…BMI, waist circumference, or WHR has been shown to be negatively associated with percent density [21][22][23][24][25][26][27][28][29][30] or absolute dense area [24-26, 29, 30], although not consistently for the latter [21,27,28], while positively associated with absolute non-dense area [21,[24][25][26][27][28][29][30]. Meanwhile, the association between weight gain during adulthood and breast density was seldom studied and led to inconsistent results [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, BMI, a measurement closely related with height, is also associated with MD. 26,27 Another study 28 found that rs11205277 was associated with two stages of height growth, the peak height velocities in infancy (PHV1) and the puberty (PHV2). Moreover Lei et al 29 confirmed the association of this SNP with stature.…”
Section: Discussionmentioning
confidence: 99%
“…While visual reading evaluates the image as a whole and may overestimate MD, semi-automatic methods compute the percentage of dense tissue taking the whole area limited by the skin into account, including the subcutaneous fat tissue that is not part of the mammary gland. 26,27 This, in turn, may imply a greater agreement between visual assessment and the absolute dense area that is not influenced by the amount of subcutaneous fat.…”
mentioning
confidence: 99%